Studi Eklesiologi GPI Papua Dan GPIB - Bayanangky Alexander Lewier; Agustinus M.L Batlajery (Program Pascasarjana UKIM, 2019)
The aim of this article is to explore how the Protestant Church in Papua (GPI-Papua) and the Protestant Church at West Indonesia (GPIB) run their mission in the world. As representatives of the church on the earth, both churches carry the same mission. As the church they are called and sent by God to fulfill their duty which is to serve the world. The method developed in this study is the document study which mneans that the study focuses on some important documents of these churches. This study found out that the presbyterial-sinodal system which is adopted by the GPI-Papua and GPIB will create or run congregation as a family. Based on this system, the church should be developed as as family of God through which the church reflects the meaning of being a church. By being a family of God, these churches should not focus more on institutional or structural and organisation aspects of the church. In contrary, the two churches should develop functional church leadership as the basic character of the church leadership.